Relationship between the strength of the hip and knee stabilizer muscles and the Y balance test performance in adolescent volleyball athletes - Guirelli, A. R.; Carvalho, C. A.; Dos Santos, J. M.; Felicio, L. R. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Due to the large number of jumping and landing movements, volleyball exerts a high demand on lower limbs, causing a high incidence of injuries. On average, 52% of volleyball injuries occur in lower limbs. Y Balance-test (YBT) is widely used to predict lower limb injury in athletes who jump, so it is important to identify whether the hip and knee stabilizer muscle strength is related to the performance of this test, since muscle strength is important for injury prevention, given the possibility of modifying these factors. The aim of this cross-sectional study was to correlate the strength of the knee and hip stabilizing muscles with YBT in adolescent volleyball athletes. METHODS: A study including 25 young volleyball players (aged 15.3 [0.85] years), was evaluated. The isometric strength of knee extensor muscles, abductors, extensors and lateral hip rotators were assessed by using the manual isometric dynamometer (Lafaytte Instrument Company®, Lafayette, IN, USA). YBT was performed three times on each posterolateral (PL), anterior (ANT) and posteromedial (PM) direction to evaluate the dominant leg. The average of 3 repetitions of isometric strength tests of tested muscles and YBT was analyzed. Pearson`s Correlation test was used for the correlation of the variables, considering as strong correlation values (0.5=r<1), with P=0.05. RESULTS: A moderate correlation was observed between the knee extensor strength and the ANT direction, and a moderate correlation between the hip extensor strength and the PL direction in YBT. CONCLUSIONS: The strength of knee and hip extensors may be one of the factors that influence the performance of YBT in adolescent volleyball players.